Development of Trust Services Market in RA - Gabrielyan Varduհi (Bulletin of Yerevan University G: Economics, 2014)
Trust property management is a perspective form of relations between economic entities aimed at increasing the efficiency of the use of different types of property. An active development of the trust is primarily due to falling profitability in the financial market where customer demand for trust services to their means significantly increases. Currently, the financial trust is the most common in Armenia. In addition to the trust related to securities and cash, prerequisites appear for real estate trust management. Testamentary trust has not yet manifested itself. The State links big plans with trust considering the possibility of effective management of the property, primarily the state-owned blocks of shares. Trust will acquire more civilized forms alongside with increasing economic literacy of financial managers and increasing demand for trust services. For purposes of its further development it is necessary to enact appropriate legislation, normative acts regulating the issues of taxation, protection of management founders before institutions offering trust services etc.